Minimizing weight of ambient air vaporizer by using identical and different number of fins along the length. (January 2021) - Jadav, Chirag; Chowdhury, Kanchan
Abstract: Ambient air vaporizer employed to vaporize liquid cryogens such as air, nitrogen, argon, natural gas etc. by using renewable energy from atmosphere is environment-friendly and energy efficient. However, the large size and price act against their ready acceptability. Moisture of air that freezes and deposits on the fin surface deteriorates the rate of heat transfer over time and increases the size of the vaporizer. Understanding the inter-relationship of the environmental condition, fin geometry and growth of frost over the fin-surface that adversely affects the flow of air through the vaporizer is the key to reduction of the size. Numerical model that incorporates the phenomena of flow boiling of cryogen inside vaporizer tubes and frost formation over the fin surface has been developed. Optimization of number of fins, fin height and vaporizer tube length using Genetic Algorithm reduced total weight of the vaporizer for 24 h of continuous vaporization of liquid nitrogen. A configuration of 6 fins shows better performance than 8 fins and 12 fins reducing weight by 6% and 20% respectively. The work further showed that using 6 fins and 8 fins (multiple fins) for equal lengths reduced the weight of the vaporizer by another 5%. Highlights: Dynamic heat transfer model is used to analyze the ambient air vaporizer. Genetic Algorithm is used for optimizing fin specification of vaporizer. Longer, but less number of fins can increase the operating time of the vaporizer. Weight of ambient air vaporizer can be minimized for a given operating time. Varying number of fins along the length may further reduce weight of vaporizer.